233k views
4 votes
Bx – 10 = f solve for x(z/2) - b = hSolve for z

1 Answer

4 votes

1) To solve for x, is to let x on the left side and the other terms and variables on the right side.

bx -10=f Add 10 to both sides

bx = f+10 Divide by b on both sides

So that's the way we solve for x.

b) For this one we multiply the whole expression by 2 and then isolate z on the left side, and the rest on the right side.

z = 2h +2b

Bx – 10 = f solve for x(z/2) - b = hSolve for z-example-1
Bx – 10 = f solve for x(z/2) - b = hSolve for z-example-2
User Matti VM
by
4.9k points